The blue planet seas of life - Fothergill, Alastair; Holmes, Martha 1961-.; Byatt, Andrew; Attenborough, David 1926-.; Fenton, George; BBC Video (Firm).; British Broadcasting Corporation; Discovery Channel (Firm).; BBC Concert Orchestra; Magdalen College (University of Oxford). Choir; BBC Worldwide Americas, Inc.; Warner Home Video (Firm). ([England] Distributed by BBC Worldwide Americas Burbank, CA Distributed by Warner Home Video, 2007)
Explores the world's oceans and is the definitive exploration of the marine world, chronicling the mysteries the deep. Discusses concepts such as evolution, the food chain, survival of the fittest, and the future of that omnipresent non-sea creature known as Man.
Disc one: Ocean world ; Frozen seas -- Disc two: Open ocean ; The deep -- Disc three: Seasonal seas ; Coral seas -- Disc four: Tidal seas ; Coasts -- Disc five: All new bonus material.
Closed captioned for the hearing impaired.
Title from container.
Originally broadcast on BBC television in 1996.
Special features: Disc 1-4: Eighty minutes of behind-the-scenes footage; interviews with producer Alastair Fothergill, cameraman Doug Allan and researcher Penny Allen; "Deep trouble" a compelling exploration of the impact of civilization on the oceans; photo galleries; fact files ; Disc 5: "Amazon abyss:" discover an amazing array of astonishing creatures living in the depths of the Amazon; "Dive to shark volcano:" venture to Cocos Island, an underwater volcano whose waters are a haven for sharks; "Between the tides:" explore the distinctive sights and sounds of an estuary in winter; "Antarctica:" survey the cold, desolate continent of Antarctica.
Music composer, George Fenton ; BBC Concert Orchestra; title music sung by Magdalen College Choir.
Narrator, David Attenborough.
Keywords: Ocean; Marine ecology; Marine ecological regions; Submarine trenches; Tide-waters.; Coasts